Association of changes in cardiorespiratory fitness with health-related quality of life in young adults with mobility disability: secondary analysis of a randomized controlled trial of mobile app versus supervised training - Anna-Maria Lampousi; Daniel Berglind; Yvonne Forsell (BMC, 2020)
Abstract Background Young adults with mobility disability report lower health-related quality of life (HRQoL) than their able-bodied peers. This study aims to examine potential differences between the effects of mobile app versus supervised training and the association of cardiorespiratory fitness change with HRQoL in young adults with mobility disability. Methods This is a secondary analysis of a parallel randomized controlled trial of a mobile app (n = 55) and a supervised health program (n = 55) that was provided for 12 weeks to 110 adults (18-45 years) with self-perceived mobility disability. Recruitment took place at rehabilitation centers in Stockholm, Sweden. Cardiorespiratory fitness was estimated from the results of a submaximal cycle ergometer test and HRQoL was assessed with the SF-36 questionnaire. Follow up was at 6 weeks, 12 weeks, and 1-year and all examinations were performed by blinded investigators. Between group differences of changes in HRQoL at follow up were estimated in intention-to-treat analysis using linear regression models. Crude and adjusted mixed-effects models estimated the associations between cardiorespiratory fitness change and HRQoL. Stratified analysis by intervention group was also performed. Results In total, 40/55 from the mobile app group and 49/55 from the supervised training group were included in the intention to treat analysis. No significant differences were observed between the effects of the two interventions on HRQoL. In both crude and adjusted models, cardiorespiratory fitness change was associated with the general health (adjusted β = 1.30, 95% CI: 0.48, 2.13) and emotional role functioning (adjusted β = 1.18, 95% CI: 0.11, 2.25) domains of SF-36. After stratification, the associations with general health (adjusted β = 1.88, 95% CI: 0.87, 2.90) and emotional role functioning (adjusted β = 1.37, 95% CI: 0.18, 2.57) were present only in the supervised group. Conclusion This study found positive associations between cardiorespiratory fitness change and HRQoL in young adults with mobility disability who received supervised training. The effects of mobile app versus supervised training on HRQoL remain unclear. Trial registration International Standard Randomized Controlled Trial Number (ISRCTN) registry ISRCTN22387524 ; Prospectively registered on February 4th, 2018.